2023
DOI: 10.3390/medicina59061136
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sodium-Glucose Cotransporter 2-Inhibitors on Steatosis and Fibrosis in Patients with Non-Alcoholic Fatty Liver Disease or Steatohepatitis and Type 2 Diabetes: A Systematic Review of Randomized Controlled Trials

Abstract: Type 2 Diabetes Mellitus (T2DM) and non-alcoholic fatty liver disease (NAFLD) are part of metabolic syndrome and share multiple causal associations. Both conditions have an alarmingly increasing incidence and lead to multiple complications, which have an impact on a variety of organs and systems, such as the kidneys, eyes, and nervous and cardiovascular systems, or may cause metabolic disruptions. Sodium-glucose cotransporter 2-inhibitors (SGLT2-i), as an antidiabetic class with well-established cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 65 publications
0
7
0
2
Order By: Relevance
“…MiR-192 could be the link between liver fibrosis and diabetic nephropathy (DN) as it is upregulated not only in our MAFLD patients but also in DN patients ( 35 ). The presence of T2DM could be one of the predictors of rapid fibrotic progression ( 36 ), and miR-192 might be one of the important biomarkers for disease evolution in MAFLD and DN.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-192 could be the link between liver fibrosis and diabetic nephropathy (DN) as it is upregulated not only in our MAFLD patients but also in DN patients ( 35 ). The presence of T2DM could be one of the predictors of rapid fibrotic progression ( 36 ), and miR-192 might be one of the important biomarkers for disease evolution in MAFLD and DN.…”
Section: Discussionmentioning
confidence: 99%
“…Ursodeoxycholic acid (UDCA) is a naturally occurring bile acid that is traditionally used to treat primary biliary cholangitis. 94 Due to its cytoprotective, immunomodulatory, and anti-apoptotic properties, there is growing interest in exploring its use in treating other liver diseases, such NAFLD. 95 , 96 Preliminary studies have posited that UDCA may improve liver function and reduce liver cell damage in NAFLD by stabilizing cell membranes, reducing harmful bile acids, and protecting against oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…[91][92][93] Specific research on tofogliflozin has shown its ability to reduce liver fat and improve indicators of liver damage in patients with both NAFLD and T2DM. 94 One trial compared tofogliflozin with glimepiride, focusing on their effects on liver histology and metabolic markers in NAFLD patients with T2DM over a 48-week period.…”
Section: Tofogliflozinmentioning
confidence: 99%
“…A meta-analysis showed that the use of SGLT2-i improved non-invasive markers of steatosis and even fibrosis in T2DM patients. It is also believed that SGLT2-i drugs may be the first choice for patients diagnosed with T2DM and NAFLD/NASH [40].…”
Section: Discussionmentioning
confidence: 99%